INTERNATIONAL BANKING IN THE CONTEXT OF THE WTO RULES AND STANDARDS - B. Loguinov (Вестник университета)
Russia has already been being a WTO country-member for 5 years and as a participant obliged to meet requirements of this organization in all sectors of the Russian economy, including banking. In the article the main rules of the banking market functioning as they are written in the Financial Annex to GATS are observed. It contains the short historic reference of the WTO standard implementations in national banking legislation. The author reviewed horizontal and vertical exceptions from the national arrangement of the presence of foreign banks in the Russian market.